(untitled) (Mongolian Journal of Geography and Geoecology, 2025)
In this study, 176 groundwater samples were collected along the floodplain of the Kherlen River to assess seasonal variations in groundwater quality. Sampling was conducted three times: twice during the spring and once during the autumn. The analysis included the use of a Piper diagram, a Gibbs diagram, and correlation analysis to evaluate temporal and spatial variations in groundwater hydrochemistry. The results revealed significant seasonal fluctuations in the concentrations of HCO₃⁻, Ca²⁺, Na⁺, Fe, F⁻, and NO₃⁻, with more pronounced spatial variations during the spring due to the dilution effect of precipitation. In both seasons, the majority of groundwater samples were classified under the Ca-HCO₃ hydrochemical type, while a few samples were identified as Na-HCO₃ and Mixed-HCO₃ types. The findings indicated that the groundwater in the study area mainly originated from rock-water interactions, with only a few samples linked to evaporation mechanisms. High Na⁺/(Na⁺+Ca²⁺) ratios and low Cl⁻/(Cl⁻+HCO₃⁻) ratios suggest that groundwater chemistry is primarily influenced by the weathering of carbonate and silicate minerals. Additionally, cation exchange processes, specifically the replacement of Ca²⁺ by Na⁺, were found to actively contribute to the hydrogeochemical evolution of the aquifer system. Correlation analysis further demonstrated that groundwater salinity is predominantly controlled by dissolved ions, as evidenced by strong positive correlations between EC and TDS. Significant associations among major ions, including Ca²⁺, Mg²⁺, Na⁺, and HCO₃⁻, highlight the influence of geochemical processes such as dolomite dissolution and the weathering of sodium-rich minerals. The positive correlation between nitrate and Ca²⁺/Mg²⁺, along with its negative correlation with HCO₃⁻, points to anthropogenic impacts-particularly from agricultural inputs-as significant contributors to groundwater contamination. These findings underscore the need for improved land and water management practices to safeguard groundwater quality in the region.